Radicalism Issues In The Qur’anic Exegesis: Muḥammad Bin Ṣāliḥ Al-‘Uthaimīn’s Thoughts on Al-Walā’, Al-Barā, Intolerance, and The Concept Of Jihad - Fawaid, Ahmad; Nashihah, Rifqiya ‘Afifatin (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2022)
Tafsr Muḥammad bin Ṣāliḥ al-’Uthaimīn not only produces a methodological implementation, but also has implications for socio-religious construction that raises issues of radicalism. This study aims to examine the elements of radicalism contained in Tafsr Muḥammad bin Ṣāliḥ al-’Uthaimīn. By using the descriptive-bibliographic method, this study maps the elements of radicalism in Tafsr Muḥammad bin Ṣāliḥ al-’Uthaimīn included in the concept of diversity and the concept of da’wah. This study shows that Tafsr Muḥammad bin Ṣāliḥ al-’Uthaimīn claims that his religious concept is the only form of the most correct and safe model. In the social sphere, Uthaimīn carries the concept of al-Walā’ (loyalty) giving the impression that Muslims should be united, close and help each other with one another, but not with infidel groups. Then in conceptualizing al-Barā’ (rejection), al-’Uthaimīn considers that other religious communities should be shunned even under certain conditions they can be fought; diversity of Muḥammad bin Ṣāliḥ al-'Uthaimīn intolerant in the theological-ritual realm. While his views on jihad, al-’Uthaimīn classifies jihad into several levels, including fighting people of other religions.